Citra Landsat 8 on Environmental Spatial Analysis for Determining the Zone of Mangrove Distribution in Langkat District - Nurhasanah; A. Hadian Pratama Hamzah; Sri Harijati (Jurnal Penelitian Pendidikan IPA, 2023)
Langkat Regency has the largest mangrove forest in North Sumatra. Lubuk Kertang Langkat Village from 2014 to 2018 there has been an increase in the area of ​​mangrove forest by 69.3 Ha. Mangroves 2014-2016. By collecting data on the pattern of mangrove distribution zones in the mangrove area, it will reduce changes in the area of ​​the mangrove area, so that the possibility of distribution of mangroves in the Langkat Regency area is known. Remote sensing using Citra Landsat 8 is part of the way to determine the distribution of mangroves. The purpose of this study was to examine the distribution of mangrove zones in the Langkat area using Citra Landsat 8. The research results found that there were 18 types of mangrove plants in Langkat district, namely Avicennia marina, Nypa fruticans, Sonneratia alba, Rizophora apiculate, Avicennia officinalis, Avicennia rumphiana, Aegiceras corniculatum, Rizophora rumphiana, Aigeceras hydrophyliacea, Scyhiphora hydrophylicea, Avicenniam marina, Scyphiphora hydrophyliacea, Soneratia alba, Aigeceras corniculatum, Lumnitzera littorea, Rhizophora apiculate, Rhizophora mucronata. the type of mangrove plant that ranks first is Rhizophora where this plant has the highest species density value of all existing mangrove species, which is equal to 900 Ind/400m. Rhizophora is a type of mangrove plant that has a fruit length of 1.9 cm, an average of 52 cm, and a fruit weight of 56 gr. The pattern of distribution of mangrove plants in groups is based on the tendency of mangrove species to inhabit their preferred environment.